Analisis Potensi Dampak Lingkungan pada Proses Produksi Urea di Industri Pupuk Menggunakan Life Cycle Assesment (LCA) - Farah Eka Putri Ramadaniati (Prosiding ESEC, 2023)
Indonesia is known as an agricultural country where the population's employment depends on the agricultural sector. As the need for agricultural products to fulfill basic needs increases, fertilizer production in Indonesia is increasing over time. Fertilizer production on a large scale will likely have negative impacts on the environment.. Processing of urea still has potential impact on environment, so that precaution and alternative are needed to create a processing that is more environmentally friendly. This study purposed to analyze potential of environmental impact and to find out the impact category with the biggest influence (hotspot) from the urea production process based on Regulation of the Minister of Environment and Forestry Number 1 of 2021 . Potential environmental impact assesment is determined using Life Cycle Assesment method trough OpenLCA 1.11.0 software. The scope of study applied in this study is gate to gate approach, consist from start processing of ammonia material up to final product urea. Based on the results of the analysis, it is known that the biggest potential impact comes from the Prilling Unit process of 429,0358 kg SO2 eq in the acidification potential category.